Diversity, structure and composition of vegetation in post-coal mining reclamation area in Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yuningsih L, Hearmansyah, Ibrahim E, Marsi. 2021. Diversity, structure and composition of vegetation in post-coal mining reclamation area in Sumatra, Indonesia. Biodiversitas 22: 3392-3400. The majority of coal mines are operated through an open-pit system which has a significant impact on the environment. Therefore, reclamation and revegetation activities are required to recover ecological sustainability. This study aimed to analyze the diversity, structure, and composition of vegetation resulting from the post-mining revegetation process in a mining concession in Sumatra, Indonesia at various intervals of post-reclamation periods, namely 11 years, 10 years, 8 years, and 5 years. Data collection was conducted by sampling with a 2.5 percent intensity. The study discovered 23 species of naturally grow understory plants and 25 species of woody plants. The stand structure at the eleventh, tenth, and eighth years of revegetation resembled an inverted J curve. The Species Richness Index (R) was determined to be low, the Shannon diversity index (H’) was is low to moderate, whereas the evenness index was moderate to high. We concluded that the structure of vegetation in the post-mining reclamation region resembled that of a natural forest ecosystem, yet the biodiversity indicators remain low and below those of natural forest. We expected the result of this study can enrich the limited knowledge of the ecology of post-mining reclamation in the tropics.
Keywords: Post-coal mining, revegetation, reclamation, vegetation